MENYOAL IDENTITAS PEREMPUAN Analisa Identitas Sosial Perempuan Sirofenisia Dalam Mrk 7:24-30 - Kartono -; Antonius Galih Arga Wiwin Aryanto (Jurnal Ledalero, 2022)
Abstract: Every narrative in the Bible has not only theological insight but also social-communal aspect. Thus, the biblical narrative contains inspiration for today's social life. One such narrative is the story of the Syrophoenician woman in Mark 7:24-30. This article studies the identity of Syrophoenician woman in the light of Social Identity Theory. This research is important because it is not common to investigate the identity of women with scientific social theory in the narrative of the Bible. By this research, we get an explanation of the identity of the Syrophoenician woman and her struggles as a woman and the mother of a daughter who is possessed by a demon. Syrophoenician woman is regainner respectable identity, namely domestic (family) affairs. Moreover, she has also gives an example for other women to be brave crossing geographical, political, cultural, and ethnic boundaries for salvation.Key words Syrophoenician Woman, Social Identity Theory, Jewish, Mediterranian, Social Identity